2022
DOI: 10.3390/jcm11071881
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Serum IgG Anti-Integrin αvβ6 Autoantibodies Is a Promising Tool in the Diagnosis of Ulcerative Colitis

Abstract: IgG anti-integrin αvβ6 autoantibodies (IgG anti-αvβ6) have been described as highly sensitive and specific markers of ulcerative colitis (UC) in the sera of Japanese inflammatory bowel disease (IBD) patients. We aimed to evaluate the diagnostic performance of IgG anti-αvβ6 as a biomarker in Swedish patients with IBD or irritable bowel syndrome (IBS). The study included adult UC (n = 59), Crohn’s disease (CD, n = 38), and IBS patients (n = 100). Partial Mayo score and Harvey–Bradshaw index were used to assess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…Rydell et al. found that the level of serum IgG anti-integrin αvβ6 autoantibodies was obviously increased in patients with UC ( 23 ), consistent with our finding that integrin αvβ6 was abundantly expressed in the intestinal epithelium of UC. We also found integrin αvβ6 expression was related with the severity of inflammation, in accordance with the previous report which through ITGB6 transgenic mouse model found that integrin β6 maintained the colon hyperresponsive to inflammatory factors and ultimately promoted the development of IBD ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Rydell et al. found that the level of serum IgG anti-integrin αvβ6 autoantibodies was obviously increased in patients with UC ( 23 ), consistent with our finding that integrin αvβ6 was abundantly expressed in the intestinal epithelium of UC. We also found integrin αvβ6 expression was related with the severity of inflammation, in accordance with the previous report which through ITGB6 transgenic mouse model found that integrin β6 maintained the colon hyperresponsive to inflammatory factors and ultimately promoted the development of IBD ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…In a study from Japan, anti-integrin αvβ6 (anti αvβ6) autoantibodies had a sensitivity of 92.0% and a specificity of 94.8% for diagnosing UC in adult patients as compared to non-IBD subjects 11 . These results were further confirmed in a Swedish cohort and extended to a Japanese pediatric population 12, 13 . Integrin αvβ6 is an epithelium-associated heterodimer that interacts with the extracellular matrix 14 and enables the activation of latent TGF-β, which is thought to be its primary role in vivo 15, 16 .…”
Section: Introductionsupporting
confidence: 63%
“…These results were further confirmed in a Swedish cohort and extended to a Japanese pediatric population 12,13 . Integrin αvβ6 is an epithelium-associated heterodimer that interacts with the extracellular matrix 14 and enables the activation of latent TGF-β, which is thought to be its primary role in vivo 15,16 .…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations